Faktor Penyebab Remaja Melakukan Hubungan Seks di Luar Nikah di Jorong Bukik Nilam Nagari Aua Nagari Aua Kuniang Kabupaten Pasaman Barat. - WATI, ELMA - (Pendidikan Sosiologi, 2014)
This research of background overshadow by existence of the problem of social which have global in this time that is problem of free seks which happened many at adolescent circle. Many from them which step into black dale without them realize. Existence of sexual motivation having meaning tendency of biologis to look for sexual comments and comments smelling sexual of others, usually from oposite gender emerge adolescent in the early and stand at bay strength as long as life. Target of this research is: for the mendeskripsikan of adolescent cause factor do/conduct coitus outside marrying in Jorong Bukik Sapphire Sub-Province of Pasaman West.this Type Research is research qualitative with descriptive type. Technique weared in election of informan is sampling purposive. Informan [at] this research that is informan is adolescent which have done/conducted coitus outside marrying, and society of niniak mamak in Jorong Bukik Sapphire of Nagari Aua Kuniang. Method data collecting [done/conducted in three way of: observation, documentation and interview. Data analysis used with model analyse data of interaktif of Miles and of Huberman.Pursuant to result of research can be concluded that: adolescent Cause factor do/conduct coitus outside marrying [in] Jorong Bukik Sapphire of Nagari Aua Kuniang Sub-Province of Pasaman West in causing by two First factor, internal factor that is factor coming from adolescent xself of itself which consist of: factor of maturity of biologis adolescent and factor feel adolescent keingintahuan to seks. Both, factor of eksternal that is factor coming from outside adolescent xself [of] itself which consist of: Religion values factor, factor role of family, media factor, friend factor coeval, place factor supporting, and factor of[is lack of control of society